2004
DOI: 10.1016/s0035-9203(03)00044-0
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability, efficacy and plasma concentrations of diethylcarbamazine and albendazole co-administration in a field study in an area endemic for lymphatic filariasis in India

Abstract: Filariasis control programmes are moving towards a strategy of repeated single-dose mass treatment of endemic populations. Using a combination, such as albendazole (ALB) to diethylcarbamazine (DEC) gives both macrofilaricidal and anti-helmintic activity. However, the safety of the combination versus DEC alone should be established in field studies in large populations prior to incorporation into national programmes. The present study compared the safety, tolerability, and efficacy of single doses of DEC 6 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
44
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 23 publications
1
44
1
Order By: Relevance
“…In addition to ivermectin, DEC has a potent microfilaricidal effect as well as 50% macrofilaricidal activity [2,[52][53][54]. The combination of DEC and albendazole has macrofilaricidal effects of between 56% and 87% [54].…”
Section: Interrupting Transmission Of Lymphatic Filariasismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to ivermectin, DEC has a potent microfilaricidal effect as well as 50% macrofilaricidal activity [2,[52][53][54]. The combination of DEC and albendazole has macrofilaricidal effects of between 56% and 87% [54].…”
Section: Interrupting Transmission Of Lymphatic Filariasismentioning
confidence: 99%
“…The combination of DEC and albendazole has macrofilaricidal effects of between 56% and 87% [54]. However, in Africa, DEC cannot be used due to co-endemicity of lymphatic filariasis and onchocerciasis; the rapid killing of O. volvulus worms results in the development of severe adverse events.…”
Section: Interrupting Transmission Of Lymphatic Filariasismentioning
confidence: 99%
“…The combination of DEC 6 mg/kg plus albendazole 400 mg resulted in the loss of 67% of FDS. 21 In contrast to these results, a more recent study showed 77.8% macrofilaricidal activity after DEC 6 mg/ kg alone compared with 43.7% after DEC plus albendazole, arguing against an additive effect of the combination of DEC + albendazole. 2 Contrary to the above-described studies with DEC alone, we saw only a trend to macrofilaricidal effects in our placebo group (33% worm nest reduction, not significant).…”
mentioning
confidence: 90%
“…Although average Mf levels dropped 99.6% versus 85.7% within a year, complete clearance was only seen in 75% and 23% of the individuals, respectively. Kshirsagar and others 21 showed in India that 67% of the DEC-treated patients were Mf negative 12 months after a single dose. Compared with these results, the 21-day doxycycline course (followed by single-dose DEC) in this study is superior, with none of the individuals staying microfilaremic.…”
mentioning
confidence: 95%
See 1 more Smart Citation